Dietary Valine Ameliorated Gut Health and Accelerated the Development of Nonalcoholic Fatty Liver Disease of Laying Hens. (25th August 2021) - Jian, Huafeng; Miao, Sasa; Liu, Yating; Wang, Xiaoming; Xu, Qianqian; Zhou, Wenting; Li, Huaiyu; Dong, Xinyang; Zou, Xiaoting
Abstract : Valine is an important essential amino acid of laying hens. Dietary supplemented with BCAAs ameliorated gut microbiota, whereas elevated blood levels of BCAAs are positively associated with obesity, insulin resistance, and diabetes in both humans and rodents. General controlled nonrepressed (GCN2) kinase plays a crucial role in regulating intestinal inflammation and hepatic fatty acid homeostasis during amino acids deficiency, while GCN2 deficient results in enhanced intestinal inflammation and developed hepatic steatosis. However, how long-term dietary valine impacts gut health and the development of nonalcoholic fatty liver disease (NAFLD) remains unknown. Hence, in the present study, we elucidated the effects of dietary valine on intestinal barrier function, microbial homeostasis, and the development of NAFLD. A total of 960 healthy 33-weeks-old laying hens were randomly divided into five experimental groups and fed with valine at the following different levels in a feeding trial that lasted 8 weeks: 0.59, 0.64, 0.69, 0.74, and 0.79%, respectively. After 8 weeks of treatment, related tissues and cecal contents were obtained for further analysis. The results showed that diet supplemented with valine ameliorated gut health by improving intestinal villus morphology, enhancing intestinal barrier, decreasing cecum pathogenic bacteria abundances such as Fusobacteriota and Deferribacterota, and inhibiting inflammatory response mediated by GCN2. However, long-term intake of high levels of dietary valine (0.74 and 0.79%) accelerated the development of NAFLD of laying hens by promoting lipogenesis and inhibiting fatty acid oxidation mediated by GCN2-eIF2 α -ATF4. Furthermore, NAFLD induced by high levels of dietary valine (0.74 and 0.79%) resulted in strengthening oxidative stress, ER stress, and inflammatory response. Our results revealed that high levels of valine are a key regulator of gut health and the adverse metabolic response to NAFLD and suggested reducing dietary valine as a new approach to preventing NAFLD of laying hens.